Differences in Interprofessional Attitudes of Doctors and Nurses at The Health Center - Kusumawati, Wiwik; Yebi, Saffana Racho Mauluda (Universitas Padjadjaran, 2025)
Interprofessional collaboration between health workers is essential to ensure quality and patient-centered healthcare delivery, especially in public health care or in Indonesian called as pusat kesehatan Masyarakat or Puskesmas. Understanding the differences in interprofessional attitudes between doctors and nurses is crucial, as these attitudes directly affect teamwork and the quality of patient care. Objective: To examine the variances of interprofessional attitudes between doctors and nurses within Puskesmas settings. This study used quantitative design and cross-sectional approach. This study was attended by 71 respondents with details of 26 doctors and 45 nurses from five different psukesmas. Data were collected using the Interprofessional Attitude Scale (IPAS) questionnaire distributed via google form media. The data were then analyzed using SPSS software with the Mann-Whitney test. The mean score for all domains was categorized as excellent (>85.06) with the highest score belonging to the “diversity and ethics” domain. While the lowest mean score was owned by the “interprofessional bias” domain with a total of (85.06), but still classified as good. Significant results were found in differences in attitudes based on profession (p = 0.000), but not on gender (p = 0.422) or work experience (p = 0.322). Interprofessional attitudes between doctors and nurses at Puskesmas are generally well-established. Significant differences in attitudes were seen based on professional roles but not based on gender or length of work experience. Efforts to strengthen the understanding of interprofessional collaboration are recommended to further improve collaboration. Keywords: Doctor, interprofessional attitudes, interprofessional collaboration, nurses, Puskesmas